Pathological characteristics and clinical prognostic analysis of intravenous leiomyomatosis: a retrospective study of 43 cases - Li, Jiezhen; Huang, Haijian; Chen, Xin; Zeng, Qiang (Frontiers in Medicine, 2025)
ObjectiveTo analyze the clinicopathological features and prognostic factors of intravenous Leiomyomatosis (IVL), a rare yet recurrent disease.MethodsThis retrospective observational study enrolled 43 patients with pathologically confirmed IVL. Clinicopathological data were collected and reviewed. Univariate analyses were performed to identify prognostic factors for IVL recurrence.ResultsClinical manifestations included increased menstrual flow (12/43), prolonged menstrual periods (18/43), pelvic mass (15/43), abdominal pain (8/43), or no symptoms (9/43). Histopathologically, tumor cells were predominantly located in the blood vessels of the uterine muscle wall and surrounding blood vessels. The tumor were composed of benign smooth muscle cells arranged in strips or bundles. Immunohistochemistry revealed that tumor cells were positive for SMA (43/43), Desmin (42/43), and Caldesmon (40/43). Incomplete resection of the lesions was identified as a risk factor for postoperative recurrence of IVL (P < 0.05). Age, menopause status, gravidity, parity, maximum diameter of IVL, uterine leiomyomas, involvement of uterine/extrauterine blood vessels, surgical methods, Ki-67 index, and mitotic figures were not associated with postoperative recurrence of IVL (P > 0.05).ConclusionIVL is a rare form of leiomyoma with potential for malignancy. Complete resection of the lesion should be performed whenever possible to improve patient prognosis.